The self-reactive FVIII T cell repertoire in healthy individuals relies on a short set of epitopes and public clonotypes - Porcheddu, Valeria; Lhomme, Gautier; Giraudet, Rémi; Correia, Evelyne; Maillère, Bernard (Frontiers in Immunology, 2024)
Non-mutated FVIII-specific CD4 T cell epitopes have been recently found to contribute to the development of inhibitors in patients with hemophilia A (HA), while auto-reactive CD4 T cells specific to FVIII circulate in the blood of healthy individuals at a frequency close to the foreign protein Ovalbumin. Thus, although FVIII is a self-protein, the central tolerance raised against FVIII appears to be low. In this study, we conducted a comprehensive analysis of the FVIII CD4 T cell repertoire in twenty-nine healthy donors. Sequencing of the CDR3β TCR region from isolated FVIII-specific CD4 T cells revealed a limited usage and pairing of TRBV and TRBJ genes, as well as a mostly hydrophobic composition of the CDR3β region according to their auto-reactivity. FVIII repertoire is dominated by few clonotypes, with only 13 clonotypes accounting for half of the FVIII response. Through a large-scale epitope mapping of the full- length FVIII sequence, we identified 18 immunodominant epitopes located in the A1, A3, C1, and C2 domains and covering half of the T-cell response. These epitopes exhibited a broad specificity for HLA-DR or DP molecules or both. T-cell priming with this reduced set of peptides revealed that highly expanded clonotypes specific to these epitopes were responsible individually for up to 32% of the total FVIII repertoire. These FVIII T cell epitopes and clonotypes were shared among HLA-unrelated donors tested and previously reported HA patients. Our study highlights the role of the auto-reactive T cell response against FVIII in HA and its similarity to the response observed in healthy individuals. Thus, it provides valuable insights for the development of new tolerance induction and deimmunization strategies.